Comparative assessment value of the use ofdisinfectants in medical institutions - A I Smirnov (RUDN Journal of Medicine, 2013)
The work was carried out economic evaluation and comparison of the value in use of various disinfectants used in health facilities. Conducted a comparative analysis of the cost of processing of surfaces and instruments with a bacterial or viral infection. Calculated the cost of working solutions and the cost of processing a surface unit.